Quantum dot spin cellular automata for realizing a quantum processor. (7th September 2015) - Bayat, Abolfazl; Creffield, Charles E; Jefferson, John H; Pepper, Michael; Bose, Sougato
Abstract: We show how single quantum dots, each hosting a singlet–triplet qubit, can be placed in arrays to build a spin quantum cellular automaton. A fast (∼10 ns) deterministic coherent singlet–triplet filtering, as opposed to current incoherent tunneling/slow-adiabatic based quantum gates (operation time ∼300 ns), can be employed to produce a two-qubit gate through capacitive (electrostatic) couplings that can operate over significant distances. This is the coherent version of the widely discussed charge and nano-magnet cellular automata, and would increase speed, reduce dissipation, and perform quantum computation while interfacing smoothly with its classical counterpart. This combines the best of two worlds—the coherence of spin pairs known from quantum technologies, and the strength and range of electrostatic couplings from the charge-based classical cellular automata. Significantly our system has zero electric dipole moment during the whole operation process, thereby increasing its charge dephasing time.